University students’ knowledge, awareness, and perception on tuberculosis (TB) disease: A literature review - Jamaludin, Thandar Soe Sumaiyah; Ismail, Nurhanis; Saidi, Sanisah; Mei Chan, Chong (Scholars Academic and Scientific Publishers, 2018)
Having knowledge of tuberculosis disease (TB) in each individual person is important in terms of understanding the signs and symptoms, spread of disease, and treatment of the disease in order to terminate the TB disease world-wide. The aim of this literature review was to evaluate the knowledge, awareness, and perception of tuberculosis (TB) disease among undergraduate students from various courses. This paper has highlighted for understanding more deeply on the university students’ knowledge, awareness, and perception towards TB diseases. However, from this study it can be concluded that the level of knowledge, awareness, and perception towards TB was varied worldwide. It was also found that, many ways to be assessed the level of knowledge, awareness, and perception towards TB disease.